Consecutive transperineal prostatic template biopsies employing cognitive and systematic approach: a single center study. (4th December 2020) - Bhat, Zubair; Bhat, Arshad; Mahmalji, Wasim
Abstract: Introduction: The role of transperineal template biopsy for prostate cancer diagnosis is well established. Pre-biopsy multiparametric magnetic resonance imaging (MRI) is used in most centers for planning of prostate biopsies and staging. Cognitive and software fusion techniques are increasingly getting popular. Methods: We retrospectively reviewed patients who underwent transperineal template biopsies from January 2016 till December 2018. This included patients on active surveillance, previous negative transrectal ultrasonography biopsies with persistently raised prostate-specific antigen/abnormal prostate on digital rectal examination and de-novo template biopsies. Two specialist uro-radiologists reported all the scans and the biopsies were performed by one experienced urologist. The cognitive biopsies were performed for PIRADS 3–5 lesions on MRI. Total of 330 patients underwent transperineal template biopsies and cognitive target biopsies were carried out in 75 patients who were included in the study. We evaluated the results as positive/negative cognitive biopsies and also according to the PIRAD scoring. Only the patients with prostate cancer on template biopsy histology were included. Results: Fifty-seven (76%) of the cognitive biopsies were positive out of total 75. Conclusions: Combined cognitive and systematic biopsies have excellent diagnostic rate especially for PIRAD 4–5 MRI areas.